Standoff : how America became ungovernable - Schneider, William, 1941- (Simon & Schuster, 2018)
"Bill Schneider, former CNN senior political analyst, takes us inside the voting booth to show how Americans vote and why their votes sometimes seem to make no practical sense. In the 1960s, a rift developed between the Old America and the New America that resulted in a populist backlash that ultimately elected Donald Trump in 2016. Schneider describes an American populism that is economically progressive and culturally conservative. Liberals are attacked as cultural elitists ("limousine liberals"), and conservatives as economic elitists ("country club conservatives"). Trump is the complete populist package. He embraces social populism (anti-immigrant), economic populism (anti-free trade), and isolationism ("America First"). Standoff examines a number of hard-fought elections to show us how we got to Trump. He asserts the power of public opinion. He points to the public that draws the line on abortion and affirmative action. He shows why an intense minority cancels a majority on gun control, immigration, small government, and international interests. Standoff tells us why fifty years of presidential contests have often been confounding. It takes us inside to watch how and why Americans pull the lever, how they choose their issues and select their leaders. It is usually values that trump economics. Standoff is required reading for an understanding of the 2016 election and the political future"--